Biodegradation of refrigerant oil (biphenyl and biphenyl ether) in a soil of the oxisol order in Lagunillas Municipality of Zulia state, Venezuela - Chirinos, Iván (2020)
In order to evaluate and determine the average time necessary to achieve the total degradation of refrigerant oils, an experiment was carried out under greenhouse conditions using as substrate a soil of the oxisol order, with pH = 4.24 (extremely acidic), with high concentration exchangeable aluminum (Al + 3) = 1.44 cmol * Kg-1 of soil, and sandy loam texture (Fa), in addition to organic fertilizer in doses of 20,000 kg * ha-1. Considering the acidity condition of the soil, agricultural lime (CaCO3) was used in doses of 2,144 kg of carbonate per hectare. The experiment was designed in factorial 4 x 3, with 4 treatments and 3 repetitions. The treatments were evaluated in flowerpots or containers where approximately 0.06 m3 of the mixture was placed (soil + waste + amendments), the waste or oil was added in doses, equivalent to 10 L * m-2. The monitoring was carried out at 15, 30 and 45 days of incubation. The results obtained for the total degradation time of biphenyl (BF) was 51 days. In the case of biphenyl ether (BFE) the average time of 116 days. In addition to the time necessary for degradation, the population of bacteria of the genus Pseudomonas, contribution of organic carbon and variation of soil pH were evaluated. Based on the results of this study, field tests may be recommended following the conditions of treatments T1 to T3.